Subjective well-being, self-esteem, and attitude towards imagined couples of yaoi fangirls in Thailand - Thanartatnattanon, Nynah; Suppapitiporn, Siriluck (Chulalongkorn Medical Journal, 2020)
Background: A number of studies on yaoi fangirls, who are interested in homoromantic/ homoerotic relationship between men, is increasing all over the world, but there are only few studies of mental health on yaoi fangirls in Thailand. Objectives: To study subjective well-being, self-esteem, and attitude towards imagined couples of yaoi fangirls, and to determine factors associated with subjective well-being of yaoi fangirls in Thailand. Methods: A cross-sectional descriptive study was conducted among literate Thai yaoi fangirls, aged from 18-yearold in August 2018. The instruments were online questionnaires, consisting of general information, Imagined Couple Attitude Scale, Self-esteem Inventory, and Thai Happiness Indicator (THI-15). Statistics used to analyze data were descriptive statistics, Chi-square test, Pearson correlation, One-way ANOVA, logistic regression, and multiple linear regression. Results: Of the total 1,745 participants, 70.5% had their attitude towards imagined couples categorized as moderate level of imagined couple worship, 46.6% had moderate self-esteem, and 38.8% were as happy as general Thai population. There was a strong positive correlation between self-esteem and subjective well-being (r = 0.745, P < 0.001), while low negative correlations were found between attitude towards imagined couples and self-esteem and subjective well-being. Of all other factors, self-esteem seemed to be the major one that can explain the 55.5% of the variance in subjective well-being. Conclusion: Most of yaoi fangirls in Thailand were found to have normal level of imagined couple worship, selfesteem, and subjective well-being. Self-esteem was a factor that could predict subjective well-being and attitude towards imagined couples. The results of this study would be beneficial for understanding yaoi fangirls in Thailand, and providing the appropriate care.